First report of Colletotrichum spp. causing diseases on Capsicum spp. in Sabah, Borneo, Malaysia - Yun, Ha Kwan; Abdul Hamid, Ahmad; Sepiah, Muid; Jaya, Seelan Sathiya Seelan (Wildlife Information Liaison Development, 2009)
Blackish or orange liquid-like spots were found on (n=100) fruits of chillies (Capsicum) sold in five local markets in Kota Kinabalu, Sabah, Malaysia. Colletotrichum gloeosporioides and C. capsici were identified as the causal agents of an anthracnose disease. This is the first report of Colletotrichum spp. as the causal agent of anthracnose infected chillies in Sabah.